Self-compassion and body-related self-conscious emotions: Examining within- and between-person variation among adolescent girls in sport. (January 2022) - Pila, E.; Gilchrist, J.D.; Kowalski, K.C.; Sabiston, C.M.
Abstract: Objectives: Self-compassion protects against the occurrence of negative body image experiences and may be particularly useful in defending against negative body- and appearance-related self-conscious emotions in sport. The aim of this study was to examine within- and between-person associations between self-compassion and appearance-related self-conscious emotions. Design & Method: In a three-year longitudinal cohort study, adolescent girls involved in organized sport ( N = 518, M age = 14.02 ± 1.38) completed yearly self-reports of self-compassion, body- and appearance-related shame, guilt, embarrassment, and envy. Results: Based on findings from multilevel models, higher levels of both average and time-varying self-compassion were associated with lower levels of body-related shame, guilt, embarrassment, and envy. Specifically, girls reported lower levels of negatively valanced self-conscious emotions when self-compassion was higher than usual. Conclusions: These findings support previous accounts on the utility of self-compassion as a buffer against negative body image experiences and extend these findings to appearance-related self-conscious emotions in the sport context. In light of the declining levels of self-compassion for girls in adolescence, it is important to focus intervention efforts on cultivating self-compassion to protect girls from negative body-related emotional experiences in sport. Highlights: Self-compassion is negatively linked to body shame, guilt, embarrassment, and envy. More self-compassionate athletes experience negative emotions less frequently. Greater self-compassion than usual is associated with less frequent negative emotions.